Multi-sensor Data Processing and Fusing Based on Kalman Filtering - Bian Guangrong; Li Hongsheng; He Ninghui (Indonesian Journal of Electrical Engineering and Computer Science, 2013)
The background of this paper is the warehouse target localization and tracking system which is composed of a number of wireless sensor nodes. Firstly this paper established a model of warehouse target localization and tracking system, then a model of multi-sensor data preprocessing and data fusion was established, and self-adaptive linear recursive method was used to eliminate outliers of the original measured data. Then least squares fitting filter was used to do filtering and denoising for the measured data. In the end, the data which were measured by multi-sensor can be fused by Kalman Filtering algorithm. Data simulation analysis shows that the use of kalman filtering algorithm for the fusion of the data measured by multi-sensor is to obtain more accurate warehouse target location data, so as to increase the positioning and tracking accuracy of the warehouse target localization and tracking system.Key Words:Wireless Sensor Network,Data Fusion,Kalman Filtering DOI: http://dx.doi.org/10.11591/telkomnika.v11i3.2195